ASSESSMENT OF LIPID DYSFUNCTION IN PATIENTS ON MAINTENANCE HAEMODIALYSIS - Altaf, Ashfaq; Halim, Abdul; Khan, Dilshad Ahmad; Khalid, Muhammad; Zuhra, Fatima -Tuz-; Saif, Imran (Journal of Ayub Medical College Abbottabad, 2007)
Background: Dyslipidaemia is a major risk factor of cardiovascular disease in patients on maintenance haemodialysis. Both increased and decreased levels of cholesterol are associated with increased cardiovascular mortality in haemodialysis patients. Objective: To assess the lipid dysfunction among patients on maintenance haemodialysis in a nephrology unit at Rawalpindi as compared with healthy individuals. Methodology: A descriptive comparative study was carried out in a nephrology unit at Rawalpindi, Pakistan. A total of 140 subjects were included consisting of 70 patients on maintenance haemodialysis (MHD) and 70 healthy controls. Body mass index (BMI) was measured according to WHO guidelines. Serum total cholesterol (TC), triglycerides (TG) and high-density lipoprotein cholesterol (HDL-C) were assayed on chemistry analyser. Low-density lipoprotein cholesterol (LDL-C) was calculated by Friedwald equation. Result: MHD patients had significantly lower BMI, mean (SD) 20.07(3.66) as compared with the controls 22.88(3.97) kg/m2 (p<0.001). The lipid profile among MHD patients and controls are given as mean (SD): (a) Total Cholesterol 3.84(1.06) vs 4.65(0.97) (p<0.001), (b) LDL-C 2.21(0.77) vs 2.93(0.71) (p<0.001), (c) HDL-C 0.95(0.166) vs 0.97(0.138) (p=NS), (d) Non HDL 2.88(0.95) vs 3.67(0.88) (p<0.0001), (e) Triglycerides 1.68(1.09) vs 1.69(0.86) (p=NS). The most common abnormality observed in haemodialysis patients was low HDL-C (81%) followed by increased Non-HDL-C (23%) and increased serum triglycerides (19%). Conclusion: It is concluded that our patients on maintenance haemodialysis have significantly low BMI, total Cholesterol, LDL-C and Non-HDL-C depicting malnutrition leading to inflammation, accelerated atherosclerosis process and cardiovascular complications. Key words: total Cholesterol, lipoproteins, BMI, haemodialysis, cardiovascular disease